A preparation method of thick film high resistance resistor based on Ts gradient and three simultaneous principles

CN122291212BActive Publication Date: 2026-11-03HAINING YUNHUANG NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610638850.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-11
Publication Date
2026-11-03
Estimated Expiration
2046-05-11

AI Technical Summary

Technical Problem

Traditional thick-film resistor pastes contain precious metal RuO2, which has high cost, narrow process window, and limited protection effect, resulting in high cost, low product yield, and poor reliability.

Method used

A hybrid conductive network was constructed by replacing Pd/RuO2/ruthenate with Ag/AgO/Ag2O. A gradient temperature sintering process was designed by combining Ts gradient and the three simultaneous principles to ensure that each functional layer is formed at the optimal temperature, thereby achieving independent optimization of each layer and good interface bonding.

Benefits of technology

It significantly reduces the amount of precious metals used, lowers material costs by 5% to 30%, improves production yield, enhances process controllability, ensures electrical performance stability and wide applicability, and meets the resistance value range of 10Ω/square to 1MΩ/square.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122291212B_ABST
    Figure CN122291212B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a thick film high resistance resistor based on Ts gradient and three simultaneous principles, and is particularly applied to the field of medium and high resistance values (10Ω / square~1MΩ / square). In view of the technical problems of high cost, narrow process window and poor reliability of the Pd / RuO2 / ruthenate system in the prior art, a mixed conductive network is constructed by using Ag to partially replace RuO2, a gradient temperature sintering process is designed based on the glass softening point gradient matching principle (Ts_G1<Ts_C1<Ts_R), the interface matching between the resistor layer R and the end conductive layer C1 is improved through the gradient temperature sintering process, the excessive diffusion of the end Ag to the resistor is reduced, and the protection effect of the glass protective layer on the functional layer is improved. The application improves the problems of electric performance dispersion and poor protection reliability under the premise of reducing the amount of noble metal, realizes the cost reduction and performance improvement of the medium and high resistance thick film resistor paste, and is suitable for the application scenarios of 10Ω / square~1MΩ / square.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic materials and component manufacturing technology, specifically to a thick film resistor paste for electronic components such as thick film resistor paste and chip resistors (wafer resistors) and a method for preparing the same paste. In particular, it relates to a method for preparing thick film high-resistance resistors based on the Ts gradient and the three simultaneous principles, which is especially suitable for application scenarios of resistor pastes in the medium to high resistance range (10Ω / square to 1MΩ / square). Background Technology

[0002] Thick-film resistor paste is a functional material formed by screen printing and high-temperature sintering onto a ceramic substrate to create a resistive film. In the medium-to-high resistance range (10Ω / square to 1MΩ / square), traditional techniques primarily rely on noble metals such as Pd / RuO2 / ruthenium terephthalate as the core conductive phase. This approach suffers from the following technical problems: First, the raw material cost is high. Medium- and high resistivity slurries rely heavily on expensive RuO2 as the core conductive phase. RuO2 is a rare and precious metal oxide with a very high price. In traditional formulations, the raw material cost of RuO2 accounts for more than 70%. Moreover, in the dense film layer formed by high-temperature sintering, a large amount of RuO2 is encapsulated by the glass phase and cannot participate in conduction. The effective utilization rate of precious metals is less than 50%, which further increases the overall cost of the slurry and seriously restricts the cost control and profit margin of downstream products.

[0003] Secondly, the process window is narrow, resulting in low product yield. Traditional processes typically use a single temperature of around 850℃ to sequentially sinter the terminal conductive layer (C1 paste), the resistive layer (R paste), and finally the glass protective layer (G1 paste). However, the optimal sintering temperatures and sintering characteristics of these three functional layers differ fundamentally: the resistive layer requires a higher temperature to form a continuous and stable conductive framework, the terminal conductive layer requires a moderate temperature to form a low-resistance ohmic contact, and the glass protective layer requires a lower temperature to avoid excessive flow that could damage the underlying structure. Single-temperature sintering can only provide a compromise and cannot simultaneously meet the optimal sintering requirements of each layer. Furthermore, excessive diffusion of Ag from the terminal conductive layer (C1 paste) into the resistive body (R layer) disrupts the integrity of the R layer's conductive network, leading to deviations in sheet resistance from the design value, temperature coefficient of resistance (TCR) drift, and discrete resistance distribution.

[0004] Third, the protective effect is limited and the reliability is poor. There is a lack of effective process design principles for matching the glass protective layer (G1 paste) with the functional layer. During the sintering process, the G1 layer often damages the conductive network of the functional layer it is protecting rather than effectively protecting it, and there is a risk of performance degradation in the long term.

[0005] To address the aforementioned issues, although some studies have attempted to adjust the formulation or sintering process, none have fundamentally altered the underlying design logic of multi-dimensional conductive network synergy and high precious metal load, resulting in a difficulty in balancing cost and performance. Summary of the Invention

[0006] The present invention adopts the proposed "Ts gradient + three-simultaneity principle" to achieve the following technical effects in the medium and high resistance range (10Ω / sq ~ 1MΩ / sq): 1. Part of Pd / RuO2 / ruthenate is replaced by Ag / AgO / Ag2O to construct a mixed conductive network, which reduces the amount of precious metal while maintaining the resistance performance, so as to reduce the material cost; 2. A gradient temperature sintering process is designed based on the glass softening point gradient matching principle (Ts_G1<Ts_C1<Ts_R), so as to realize independent optimization of the performance of each functional layer and good interfacial bonding; 3. A paste system and method that can stably prepare thick film resistors in a wide range from 10Ω / sq to 1MΩ / sq are provided.

[0007] The technical solution and core innovation points of the present solution are as follows: Adopt the system design principle: The technical solution of the present invention strictly follows the proposed "Ts gradient and three-simultaneity principle": Simultaneity in design: The resistor paste, termination paste and protective layer paste must follow the Ts gradient matching principle (Ts_G1<Ts_C1<Ts_R) at the design stage, and the three are designed as a complete system, rather than being pieced together after independent design.

[0008] Simultaneity in sintering: The three layers of the resistor layer R, the termination conductive layer C1 and the protective layer G1 must be applied in sequence according to the specific sintering temperature window: First stage sintering (850-860°C): T1>Ts_R + 50°C (the superheat is above 50°C to ensure full densification of the glass phase of the resistor layer R), where T1 is the first temperature of the first stage sintering, and Ts_R is the glass phase softening point temperature of the glass phase of the resistor paste; Second stage sintering (600-620°C): Ts_C1 + 50°C<T2<Ts_R (the superheat is above 50°C to ensure densification of the termination conductive layer C1 while protecting the resistor layer), where T2 is the second temperature of the second stage sintering, and Ts_C1 is the glass phase softening point temperature of the glass phase of the termination paste; Third stage sintering (500-520°C): Ts_G1 + 50°C<T3<Ts_C1 (the superheat is above 50°C to ensure densification of the protective layer G1 while protecting the termination conductive layer C1), where T3 is the third temperature of the third stage sintering, and Ts_G1 is the glass phase softening point temperature of the glass phase of the protective layer paste.

[0009] Simultaneity in application: The resistor layer R, the termination conductive layer C1 and the protective layer G1 work synergistically as an integrated system, and any design adjustment of any layer needs to evaluate the impact on the overall performance.

[0010] In response to the specific challenges of medium and high resistance, the present invention carries out the following key material innovations under the framework of the three-simultaneity principle: In some embodiments, the glass phase softening point temperature of the protective layer slurry ranges from 350 to 500°C, the glass phase softening point temperature of the end electrode slurry ranges from 500 to 600°C, and the glass phase softening point temperature of the resistive slurry ranges from 620 to 750°C.

[0011] The typical glass phase Ts ranges of each layer are as follows: Ts of the resistive layer R: 620-750°C; Ts of the end electrode conductive layer C1: 510-530°C; Ts of the protective layer G1: 350-370°C.

[0012] Based on the Ts gradient principle, the sintering temperature window of the end electrode conductive layer is set as: Ts_C1 + 50°C < T2 < Ts_R, which ensures that the glass phase of the end electrode conductive layer is melted and densified while the integrity of the conductive network of the resistive layer is protected.

[0013] The specific Ts difference ranges of each phase are as follows: ΔT1 = T1 - (Ts_R + 50°C) > 0: superheat degree of the resistive layer R, typical range is >50°C - ΔT2 = T2 - (Ts_C1 + 50°C) > 0: superheat degree of the end electrode conductive layer C1, typical range is >50°C - ΔT3 = T3 - (Ts_G1 + 50°C) > 0: superheat degree of the protective layer G1, typical range is >50°C - ΔT_total = T1 - Ts_G1: typical total temperature difference range is 200°C ~ 350°C.

[0014] Based on the above Ts gradient principle, the sintering temperatures T1 / T2 / T3 of the present invention are each set to be 50°C or more of superheat above the respective glass phase Ts, so as to ensure the formation of excellent network characteristics and lap interface characteristics per se.

[0015] Material innovation 1: In the conductive phase of the resistive slurry, Ag is used to partially replace Pd / RuO2 / ruethenate to construct a hybrid conductive network that balances cost and performance.

[0016] Material innovation 2: The single physical anchoring property formed by sintering the end electrode slurry and the resistive slurry is innovatively upgraded to physical anchoring and chemical metal bond anchoring.

[0017] Process innovation: A gradient temperature sintering process (850°C / 10min → 620°C / 10min → 520°C / 3min) is adopted to sequentially solidify the resistive layer and the terminal conductive layer to form an ohmic contact and a protective layer; from system design to system implementation, the system ultimately achieves the optimal balance between cost and performance.

[0018] The overall technical solution of this invention lies in constructing an "RCG three-layer composite system" with resistive paste as the core functional layer and terminal conductive paste and glass protective layer paste as auxiliary layers. To ensure that the auxiliary layer process does not affect the performance of the core layer, this invention proposes a key Ts gradient matching design principle, such as... Figure 1 As shown, the softening point temperatures of the glass phases used in each layer must satisfy a strict decreasing relationship: Ts of the protective layer slurry < Ts of the end slurry < Ts of the resistance slurry. This principle is the theoretical foundation for achieving subsequent gradient temperature sintering and ensuring independent optimization of each layer and good interfacial bonding.

[0019] At the material level, the second core aspect of this invention is the innovative upgrade of the overlap system design technology between the end conductive layer C1 and the resistive layer R. In order to successfully implement the Ts gradient matching principle, if the overlap technology between the end conductive layer C1 and the resistive layer R is not upgraded, the physical anchoring strength of Ag and RuO2 will inevitably be weakened. As the saying goes, one must increase for the other to decrease, otherwise the balance will be broken. Therefore, the second core technology is to upgrade the single physical anchoring performance formed by the sintering of the end paste and the resistive paste to physical anchoring + chemical metal bond anchoring.

[0020] Correspondingly, this solution provides a method for fabricating thick-film high-resistivity resistors based on the Ts gradient and the three-simultaneity principle, including the following steps: A resistive paste is prepared by mixing silver powder, composite powder and organic carrier phase. The resistive paste is printed on a substrate and sintered at 850~860°C for 5~10 min to form a resistive layer with a mixed conductive network structure. The composite powder is a composite composition of RuO2 or lead ruthenate and glass powder. A special glass phase, compounded silver powder, and organic carrier are mixed to obtain an end paste. The end paste is printed on the end position of the hybrid conductive network structure and sintered at 600~620°C for 5~10 minutes to form an end conductive layer.

[0021] Furthermore, a protective layer is printed on the conductive and resistive layers at the ends. The protective layer paste is printed directly above the hybrid conductive network structure and sintered at 500~520°C for 3~5 minutes to form the protective layer.

[0022] Regarding the end slurry in this solution: The end-cap slurry provided in this solution can form a strong anchor at the interface of the conductive network in the resistive layer. The core function of the end-cap conductive layer C1 is to establish excellent ohmic contact between the resistive network and the end cap and to derive the resistance. At the same time, Ts gradient matching ensures good interfacial bonding with the resistive layer. However, the main conductive phase in the resistive layer from 10Ω / square to 1MΩ / square is RuO2. In essence, the anchoring between RuO2 and Ag in the end-cap slurry is a weak connection, which poses a significant challenge to various electrical properties of the resistor, such as ESD degradation and microcracks at the interface. Therefore, this invention innovatively designs a special solution to solve this problem.

[0023] In this scheme, a special glass phase modified with RuO2 is used as the glass phase. Correspondingly, the special glass phase modified with RuO2, compounded silver powder and organic carrier are mixed to obtain the end slurry. The ruthenium dioxide present in the special glass phase modified with RuO2 reacts with the ruthenium dioxide in the resistive conductive network during the sintering process to form strong metallic bonds.

[0024] To address the issue that Ag in the end-cap slurry cannot form a strong, alloy-level anchorage with RuO2 in the resistive layer, this invention introduces a nano-ruthenium oxide-modified glass phase into the matching end-cap slurry. The design of this nano-ruthenium oxide-modified glass phase achieves two significant improvements: 1) The sintering of the end paste and the resistance paste to form a metal bond-level anchoring overlap (RuO2-RuO2) has been achieved, which greatly upgrades the traditional arbitrary matching of end conductive layers, which leads to various random quality degradation problems caused by the physical anchoring (weak connection) of the interface overlap.

[0025] 2) At the same time, it can control the high-temperature viscosity and wettability of the glass phase, suppress the dissolution-precipitation effect of silver in the glass liquid phase, change the sintering of the silver powder at the end from liquid phase sintering to solid-like phase sintering, greatly reduce the high-temperature migration and interface diffusion of silver, and greatly reduce its impact on the integrity of the conductive network of the solidified resistive layer.

[0026] In some embodiments, the RuO2-modified special glass phase in the resistive paste contains 68-74% glass mixed powder, 8-12% nano-ruthenium oxide, and 15-21% inorganic phase, with the sum of the mass percentages of each group being 100%.

[0027] In some embodiments, a special glass phase modified with RuO2 is obtained by ball milling and dispersion, and the specific surface area of ​​the nano-ruthenium oxide is 60~100m². 2 / g, with an ultra-high specific surface area suitable for nanoscale modification requirements, can ensure uniform dispersion of nano-ruthenium oxide in glass powder. Precise modification of the glass phase can be achieved with a very small amount of ruthenium, maximizing the utilization efficiency of ruthenium. This replaces the inefficient mode of adding large amounts of nano-ruthenium oxide as a conductive phase in traditional solutions, significantly reducing the amount of ruthenium used. Moreover, the average particle size of nano-ruthenium oxide is 10~30nm. The ultra-small nanoparticle size can ensure that nano-ruthenium oxide is not agglomerated and is uniformly dispersed in the glass phase. During sintering, it can stably modify the glass phase and optimize the interface performance, while not affecting the flatness and structural uniformity of the film due to excessively large particles.

[0028] In some embodiments, the glass powder mixture in the RuO2-modified special glass phase contains two types of glass: a first glass and a second glass. The first glass is the main component, containing SiO2, PbO, B2O3, ZrO2, Na2O, TiO2, ZnO, and Li2O. The second glass is the auxiliary component, containing SiO2, PbO, B2O3, and ZnO. The first glass serves as a binder phase, and the second glass is used to adjust the overall glass softening point.

[0029] Furthermore, the first glass powder contains 30-36% SiO2, 40-50% PbO, 1-5% B2O3, 1-5% ZrO2, and 7-12% Na2O, TiO2, ZnO, and Li2O, with the sum of the mass percentages of each component being 100%. The second glass powder contains 5-8% SiO2, 79-83% PbO, 9-12% B2O3, and the remainder ZnO, with both types of glass totaling 100%.

[0030] The inorganic phase contains 100% TiO2.

[0031] In some embodiments, glass powder, nano-ruthenium oxide and inorganic phase are mixed and then ZrO2 balls are added for ball milling, wherein the material-to-ball ratio is 1:8~12 and the ball milling is performed for 0.5~1.5 hours.

[0032] At the materials level, one of the core aspects of this invention is the design of a conductive phase in which Ag partially replaces Pd / RuO2 / ruthenium salt. By adjusting the ratio of Ag to RuO2 / ruthenium salt, precise control of the conductive network can be achieved within a target resistance range of 10 Ω / square to 1 MΩ / square, while significantly reducing dependence on expensive Pd / RuO2 or ruthenium salt.

[0033] Regarding the resistive layer in this scheme: A resistive paste is prepared by mixing silver powder, composite powder and organic carrier phase. The resistive paste is printed on a substrate and sintered at 850~860°C for 5~10 min to form a resistive layer with a mixed conductive network structure. The composite powder is a composite composition of RuO2 or lead ruthenate and glass powder. The proportion of silver powder is 0~28%.

[0034] In some embodiments, the composite powder contains at least two glass powders with different glass softening point temperatures, wherein the glass powder with the highest glass softening point temperature in the composite powder has a glass phase softening point temperature range of 700-800°C, and the glass powder with the lowest glass softening point temperature in the composite powder has a glass phase softening point temperature range of 450-550°C.

[0035] In some embodiments, a resistive paste is obtained by mixing 30-53% of composite powder, 7-28% of silver powder, and 38-42% of organic carrier, with the sum of the mass percentages of each component being 100%.

[0036] Regarding the end slurry in this solution: In some embodiments, a terminal slurry is obtained by mixing 9-13% of a RuO2-modified special glass phase, 61-67% of a compounded silver powder, and 22-28% of an organic carrier, with the sum of the mass percentages of each component being 100%.

[0037] That is, the typical formulation of the end-cap slurry: Special glass phase modified with RuO2: 9~13%Ts: 521°C; Compound silver powder: 61~67%; Organic carriers (ethyl cellulose, terpineol, etc.): 22-28%; Total: The sum of the mass percentages of all components is 100%.

[0038] That is, a special glass phase modified with RuO2 is obtained by mixing a glass phase, nano-ruthenium oxide and an inorganic phase and dispersing them by ball milling. The special glass phase modified with RuO2, compounded silver powder and organic carrier are then mixed to obtain the end slurry.

[0039] Regarding the protective layer slurry in this solution: Typical formulation of protective layer slurry: Special glass phase: 60~64%; Ts: 361°C; Inorganic powder: 8~12%; Organic powder: 0.1~0.5%; Organic carriers (ethyl cellulose, terpineol, etc.): 13-17%; Total: The sum of the mass percentages of all components is 100%.

[0040] In some embodiments, a protective layer slurry is obtained by mixing 60-64% of a special glass phase, 8-12% of inorganic powder and 13-17% of organic carrier, with the sum of the mass percentages of each component being 100%.

[0041] like Figure 2 As shown, the sintering system of this scheme includes a gradient temperature sintering process flow. The key to the preparation method lies in the gradient temperature sintering process, which strictly follows the aforementioned Ts gradient principle: The first stage, high-temperature sintering of the resistive layer R, involves printing the resistive paste onto the substrate and sintering it at 850-860°C for 5-10 minutes. This stage aims to fully sinter the resistive paste, forming a stable resistive body and establishing a basic conductive framework.

[0042] The second stage involves the medium-temperature sintering of the conductive layer at the tip: The tip paste is printed onto the resistive layer R and sintered at 600-620°C for 5-10 minutes. This stage deposits the tip paste (conductive layer), establishing a resistive network and ohmic contact with the tip, thus deriving the resistance.

[0043] The third stage of the protective layer is sintered at low temperature: Finally, the protective paste is printed and sintered at 500~520°C to form a protective layer. During this stage, the protective paste is deposited to form a dense glass protective layer on the surface of the resistive layer, which plays a role in moisture protection, corrosion protection and mechanical protection.

[0044] Beneficial effects: Compared with the prior art, the present invention has the following beneficial effects: 1) Significant cost advantage: By adopting a mixed conductive phase design that partially replaces Pd / RuO2 / ruthenate with Ag, the cost of precious metal raw materials is significantly reduced. Preliminary estimates suggest that material costs can be reduced by approximately 5% to 30%.

[0045] 2) Excellent electrical properties and stability: The gradient temperature sintering process based on the Ts gradient matching principle ensures that each functional layer is formed at its optimal temperature, resulting in good interfacial bonding, low contact resistance and excellent temperature coefficient of resistance.

[0046] 3) Enhanced process controllability: Gradient temperature sintering process provides a wider process window, reduces sensitivity to fluctuations in sintering temperature curves, and helps improve production yield and product consistency.

[0047] 4) Wide application adaptability: This technical solution successfully achieves a wide resistance range from 10Ω / square to 1MΩ / square, and through flexible adjustment of the material system, it can meet the differentiated performance and cost requirements of different medium and high resistance application scenarios. Attached Figure Description

[0048] Figure 1 It is a gradient relationship diagram of the softening point temperature of the glass phases used in each layer.

[0049] Figure 2 This is a schematic diagram of the sintering process. Detailed Implementation

[0050] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments obtained by a person of ordinary skill in the art based on the embodiments of the present invention shall fall within the protection scope of the present invention.

[0051] Those skilled in the art should understand that, in the disclosure of the present invention, the orientation or positional relationships indicated by the terms "longitudinal", "transverse", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer" and the like are based on the orientation or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the indicated device or element must have a specific orientation, be constructed and operated in a specific orientation, therefore, the above terms shall not be construed as limiting the present invention.

[0052] The following definitions are specially made for the convenience of describing the subsequent embodiments: IP powder: A composite powder prepared by traditional formulas and processes, which is a powder composited by a glass phase and a conductive phase of RuO₂ or lead ruthenate through a ball milling process.

[0053] Organic vehicle: A homogeneous organic vehicle produced through high temperature and stirring processes with 20% ethyl cellulose and 80% terpineol.

[0054] Industry requirements for chip resistors: The resistance drift shall be less than 5% after the protective layer is covered.

[0055] Embodiment 1: Preparation of 10Ω / square grade resistor RFD053: The resistor paste, end termination paste and protective layer paste are synchronously designed based on the glass softening point (Ts_G1<Ts_C1<Ts_R), and Pd powder is completely replaced by silver powder; Preparation of the resistor paste: Take 31.2 parts of IP, 24.5+4.3 parts of silver (4.3 parts replace Pd), and 40 parts of organic vehicle, mix them uniformly and disperse uniformly.

[0056] Preparation of the end termination paste: Take 14.8 parts of the glass phase, 62 parts of compounded silver powder, and 23.2 parts of organic vehicle, mix them and disperse uniformly.

[0057] Preparation of the protective paste: Take 74 parts of the glass phase and 26 parts of organic vehicle, mix them and disperse uniformly.

[0058] Sintering process: The resistor layer is sintered at 850°C for 10 minutes, the end termination conductive layer at 620°C for 10 minutes, and the protective layer at 520°C for 3 minutes.

[0059] Test results: sheet resistance 12.84Ω / sq, HTCR 80.8 ppm / °C, CTCR 0.1 ppm / °C, ESD 4.17, G1 change rate 1.38%.

[0060] Comparative Example 1 (same R + conventional blind matching + conventional sintering): Preparation of resistance paste: take 31.2 parts of IP, 24.5 + 4.3 parts of silver (4.3 parts replacing Pd), and 40 parts of organic vehicle, mix uniformly and disperse uniformly.

[0061] Preparation of end termination paste: blind matching.

[0062] Preparation of protective paste: blind matching.

[0063] Sintering process: first, the end termination conductive layer at 850°C for 10 minutes, then the resistance layer at 850°C for 10 minutes, and finally the protective layer at 600°C for 3 minutes.

[0064] Test results: sheet resistance 11.17 Ω / sq, HTCR 90.9 ppm / °C, CTCR 6.8 ppm / °C, ESD 5.28, G1 change rate: 1.03%.

[0065] The test data of Example 1 and Comparative Example 1 are shown in Table 1 below: Table 1 Test Data Table of Example 1 and Comparative Example 1 .

[0066] Detailed description of Example 2: Preparation of 100Ω / sq level resistor RFC969-1: The resistance paste, end termination paste and protective layer paste are designed synchronously based on the glass softening point (Ts_G1<Ts_C1<Ts_R), and 19% of the IP powder is replaced by silver powder.

[0067] Preparation of resistance paste: take 41 parts of IP602; 19 parts of silver powder; 60 parts of total powder; 40 parts of organic vehicle, mix uniformly and disperse uniformly.

[0068] Preparation of protective paste: take 74 parts of this glass phase and 26 parts of organic vehicle, mix and disperse uniformly.

[0069] Sintering process: the resistance layer at 850°C for 10 minutes, the end termination conductive layer at 620°C for 10 minutes, and the protective layer at 520°C for 3 minutes.

[0070] Test results: sheet resistance 113 Ω / sq, HTCR -62 ppm / °C, CTCR -165 ppm / °C, ESD 2.73, G1 change rate 1.28%.

[0071] Comparative Example 2 (Pulp prepared by conventional process + conventional blind mixing + conventional sintering) DFA142: Preparation of resistive paste: Take 60 parts of IP602 powder and 40 parts of organic carrier, and mix them evenly.

[0072] Preparation of end slurry: blind mixing.

[0073] Preparation of protective slurry: blind mixing.

[0074] Sintering process: first conductive layer 850°C / 10 minutes, then resistive layer 850°C / 10 minutes, and finally protective layer 600°C / 3 minutes.

[0075] Test results: Sheet resistance 115.97 Ω / square, HTCR 51.2 ppm / °C, CTCR -34.1 ppm / °C, ESD 1.37, G1 change rate: 7%.

[0076] Comparative Example 3 (same R + traditional blind mixing + traditional sintering): Preparation of resistive paste: Take 41 parts of IP602; 19 parts of silver powder; 60 parts of powder in total; and 40 parts of organic carrier, mix them evenly and disperse them evenly.

[0077] Preparation of end-point slurry: blind mixing Preparation of protective slurry: blind mixing Sintering process: first conductive layer 850°C / 10 minutes, then resistive layer 850°C / 10 minutes, and finally protective layer 600°C / 3 minutes.

[0078] Test results: Sheet resistance 94 Ω / square, HTCR 14 ppm / °C, CTCR -73 ppm / °C, ESD 0.89, G1 change rate 17.26%.

[0079] The test data for Example 2 and Comparative Examples 2-3 are shown in Table 2 below: Table 2 Test Data Table for Example 2 and Comparative Examples 2-3

[0080] Comprehensive conclusion: Example 2 (RFC969-1) adopts the Ts gradient matching and gradient temperature sintering process, and exhibits excellent performance in 100 Ω / sq level resistors. The G1 change rate is 1.28%, which is 85% lower than that of Comparative Example 2 (7%) and 93% lower than that of Comparative Example 3 (17.26%), far below the 5% industry standard, greatly improving mass production feasibility; the ESD performance is 2.73, meeting the industry standard; the cost is reduced by about 30% compared with the traditional process. In the horizontal comparison of each example, although Comparative Example 1 has a low temperature coefficient, its G1 change rate exceeds the industry standard; Comparative Example 2 has the optimal temperature coefficient (HTCR is only 14 ppm / °C), but its G1 drift is as high as 17.26%, far exceeding the industry standard and failing to meet the mass production requirements. Example 2 achieves the best balance between process stability and cost. In summary, the gradient system design based on Ts_G1<Ts_C1<Ts_R, combined with the gradient temperature sintering process, can significantly improve the process stability of thick film resistors (the G1 change rate is reduced by 93%), while reducing production costs, and has a particularly remarkable effect on solving the mass production bottleneck problem of resistance drift after G1 sintering.

[0081] Example 3: Preparation of 1 KΩ / sq level resistor RFC978: Synchronously design the resistance paste, termination paste and protective layer paste based on the glass softening point (Ts_G1<Ts_C1<Ts_R), and replace 14% of the IP powder with silver powder.

[0082] Preparation of resistance paste: Take 46 parts of IP, 14 parts of silver, and 40 parts of organic vehicle, mix them uniformly, and disperse them uniformly.

[0083] Preparation of termination paste: Take 14.8 parts of the glass phase, 62 parts of compounded silver powder, and 23.2 parts of organic vehicle, mix them, and disperse them uniformly.

[0084] Preparation of protective paste: Take 74 parts of the glass phase and 26 parts of organic vehicle, mix them, and disperse them uniformly.

[0085] Sintering process: The resistance layer is treated at 850°C for 10 minutes, the termination conductive layer at 620°C for 10 minutes, and the protective layer at 520°C for 3 minutes.

[0086] Test results: Sheet resistance is 1.07 KΩ / sq, HTCR is 149.6 ppm / °C, CTCR is 67.5 ppm / °C, ESD is 6.99, and G1 change rate is 1.31%.

[0087] Conclusion: Example 3 (RFC978) adopts the Ts gradient matching and gradient temperature sintering process, the G1 change rate of the 1KΩ / sq level resistor is only 1.31%, and the ESD performance reaches 6.99, which meets the industry standard. It shows that the gradient system design based on Ts_G1<Ts_C1<Ts_R is also effective in the medium and high resistance range, with excellent process stability. Compared with the traditional formula, the cost is reduced by 20%.

[0088] Example 4 Preparation of 10KΩ / sq level resistor RFB968-3B: Based on the glass softening point (Ts_G1<Ts_C1<Ts_R), the resistor paste, termination paste and protective paste are designed synchronously, and 7% of the IP powder is replaced by silver powder.

[0089] Preparation of resistor paste: Take 53 parts of IP, 7 parts of silver powder, and 40 parts of organic vehicle, mix and disperse uniformly.

[0090] Preparation of termination paste: Take 14.8 parts of this glass phase, 62 parts of compound silver powder, and 23.2 parts of organic vehicle, mix and disperse uniformly.

[0091] Preparation of protective paste: Take 74 parts of this glass phase and 26 parts of organic vehicle, mix and disperse uniformly.

[0092] Sintering process: Resistor layer at 850°C for 10 minutes, termination conductive layer at 620°C for 10 minutes, protective layer at 520°C for 3 minutes.

[0093] Test results: Sheet resistance 12.48 KΩ / sq, HTCR 10 ppm / °C, CTCR -64 ppm / °C, ESD 11.41, G1 change rate 0.31%.

[0094] Comparative Example 4 (same R + traditional blind matching + traditional sintering): Preparation of resistor paste: Take 60 parts of IP and 40 parts of organic vehicle, mix uniformly.

[0095] Preparation of termination paste: Blind matching.

[0096] Preparation of protective paste: Blind matching.

[0097] Sintering process: The termination conductive layer is first treated at 850°C for 10 minutes, then the resistor layer at 850°C for 10 minutes, and finally the protective layer at 600°C for 3 minutes.

[0098] Test results: Sheet resistance 4.09 KΩ / sq, HTCR 239.3 ppm / °C, CTCR 196.8 ppm / °C, ESD 12.01, G1 change rate 7.87%.

[0099] The test data table for Example 4 and Comparative Example 4 is shown in Table 4 below: Table 4 Test Data Table of Example 4 and Comparative Example 4 .

[0100] Example 5: Preparation of 100 KΩ / sq grade resistor RFC996-1: The resistance paste, termination paste and protective paste are synchronously designed based on the glass softening point (Ts_G1<Ts_C1<Ts_R), and 7% of IP powder is replaced by silver powder: Preparation of resistance paste: Take 53 parts of IP, 7 parts of silver powder, and 40 parts of organic vehicle, mix and disperse uniformly. Preparation of termination paste: Take 14.8 parts of the glass phase, 62 parts of compounded silver powder, and 23.2 parts of organic vehicle, mix and disperse uniformly.

[0101] Preparation of protective paste: Take 74 parts of the glass phase and 26 parts of organic vehicle, mix and disperse uniformly.

[0102] Sintering process: Resistance layer at 850°C for 10 minutes, termination conductive layer at 620°C for 10 minutes, protective layer at 520°C for 3 minutes.

[0103] Test results: Sheet resistance 124.37 KΩ / sq, HTCR 95.3 ppm / °C, CTCR 61 ppm / °C, ESD 5.83, G1 change rate 0.26%.

[0104] Comparative Example 5 (same R + traditional blind matching + traditional sintering): Preparation of resistance paste: Take 53 parts of IP, 7 parts of silver powder, and 40 parts of organic vehicle, mix and disperse uniformly.

[0105] Preparation of termination paste: Blind matching.

[0106] Preparation of protective paste: Blind matching.

[0107] Sintering process: First the termination conductive layer at 850°C for 10 minutes, then the resistance layer at 850°C for 10 minutes, and finally the protective layer at 600°C for 3 minutes.

[0108] Test results: Sheet resistance 87.1 KΩ / sq, HTCR 111.3 ppm / °C, CTCR 79.3 ppm / °C, ESD 11.64, G1 change rate 18.45%.

[0109] The test data table for Example 5 and Comparative Example 5 is shown in Table 5 below: Table 5 Test Data Table of Example 5 and Comparative Example 5 .

[0110] Example 5 (RFC996-1) adopts the Ts gradient matching and gradient temperature sintering process, and exhibits excellent performance in resistors at the 100KΩ / sq level: the temperature coefficients HTCR (95.3 ppm / °C) and CTCR (61 ppm / °C) are lower than those of the comparative example (111.3 ppm / °C, 79.3 ppm / °C), with stable temperature characteristics. The G1 change rate is 0.26%, which is close to zero compared with the 18.45% of the comparative example, far lower than the 5% industry standard, while the value of the comparative example is 3~4 times more than the 5% industry standard, so the mass production feasibility is significantly improved. The ESD performance (5.83 vs 11.64) is similar and meets the industry standard. It shows that the gradient system design based on Ts_G1<Ts_C1<Ts_R can effectively solve the problems of temperature stability and process stability of high-resistance end resistors.

[0111] Example 6 Preparation of 1MΩ / sq level resistor RFD027: Based on the glass softening point (Ts_G1<Ts_C1<Ts_R), the resistor paste, termination paste and protective paste are designed synchronously, and 7% of the IP powder is replaced by silver powder.

[0112] Preparation of resistor paste: take 53 parts of IP, 7 parts of silver powder, and 40 parts of organic vehicle, mix and disperse uniformly.

[0113] Preparation of termination paste: take 14.8 parts of this glass phase, 62 parts of compounded silver powder, and 23.2 parts of organic vehicle, mix and disperse uniformly.

[0114] Preparation of protective paste: take 74 parts of this glass phase and 26 parts of organic vehicle, mix and disperse uniformly.

[0115] Sintering process: 850°C for 10 minutes for the resistor layer, 620°C for 10 minutes for the termination conductive layer, and 520°C for 3 minutes for the protective layer.

[0116] Test results: sheet resistance 0.78 MΩ / sq, HTCR -72 ppm / °C, CTCR -179 ppm / °C, ESD 1.06, G1 change rate 0.14%.

[0117] Comparative Example 6 (same R + traditional blind matching + traditional sintering): Preparation of resistor paste: take 53 parts of IP, 7 parts of silver powder, and 40 parts of organic vehicle, mix and disperse uniformly.

[0118] Preparation of termination paste: blind matching.

[0119] Preparation of protective paste: blind matching.

[0120] Sintering process: first, the end conductive layer is sintered at 850°C for 10 minutes, then the resistive layer is sintered at 850°C for 10 minutes, and finally the protective layer is sintered at 600°C for 3 minutes.

[0121] Test results: sheet resistance 0.42 MΩ / sq, HTCR -78.4 ppm / °C, CTCR -192.8 ppm / °C, ESD 0.21, G1 change rate 12.78% The test data for Example 6 and Comparative Example 6 is shown in Table 6 below: Table 6 Test Data Table of Example 6 and Comparative Example 6 .

[0122] Example 6 (RFD027) adopts the Ts gradient matching and gradient temperature sintering process, and exhibits excellent performance in resistors of the 1MΩ / sq level: the measured sheet resistance is closer to the target value of 1 MΩ / sq, the absolute values of the temperature coefficients HTCR and CTCR are closer to the target zero point, the G1 post-sintering resistance change rate (0.14% vs. 12.78%) is less than the industry standard of 5% for the example, and more than twice the industry standard for the comparative example, which significantly improves mass production feasibility. It shows that the gradient system design based on Ts_G1<Ts_C1<Ts_R can effectively solve the temperature stability and process stability problems of high-resistance end resistors.

[0123] The experimental data for each example and comparative example is shown in Table 7 below: Table 7 Experimental Data Table of Each Example and Comparative Example

[0124]

[0125]

[0126]

[0127]

[0128] .

[0129] Those skilled in the art shall understand that the various technical features of the above examples can be combined arbitrarily. For the sake of brevity of description, all possible combinations of the various technical features in the above examples have not been described. However, as long as there is no contradiction in the combination of these technical features, all such combinations shall be regarded as within the scope recorded in this specification.

[0130] The above embodiments are merely illustrative of several implementation methods of this application, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of this application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims.

Claims

1. A method for fabricating a thick-film high-resistivity resistor based on the Ts gradient and the three-simultaneity principle, characterized in that, Includes the following steps: A resistive paste is prepared by mixing silver powder, composite powder and organic carrier phase. The resistive paste is printed on a substrate and sintered at 850~860°C for 5~10 min to form a resistive layer with a mixed conductive network structure. The composite powder is RuO2 and glass powder, or a composite composition of lead ruthenate and glass powder. A special glass phase modified with RuO2, compounded silver powder, and organic carrier are mixed to obtain an end paste. The end paste is printed on the end position of the mixed conductive network structure and sintered at 600~620°C for 5~10 min to form an end conductive layer. Ruthenium dioxide present in the special glass phase modified with RuO2 reacts with ruthenium dioxide in the resistive conductive network during sintering to form strong metallic bonds. The glass powder mixture in the special glass phase modified with RuO2 contains two types of glass: a first glass and a second glass. The first glass is the main component, containing SiO2, PbO, B2O3, ZrO2, Na2O, TiO2, ZnO, and Li2O. The second glass is the auxiliary component, containing SiO2, PbO, B2O3, and ZnO. The first glass serves as a binder phase, and the second glass is used to adjust the overall glass softening point. A protective layer is printed on the conductive and resistive layers at the ends. The protective layer paste is printed directly above the hybrid conductive network structure and sintered at 500~520°C for 3~5 minutes to form the protective layer.

2. The method for preparing a thick-film high-resistivity resistor based on the Ts gradient and the three-simultaneity principle according to claim 1, characterized in that, A resistive paste is obtained by mixing 30-53% composite powder, 7-28% silver powder, and 38-42% organic carrier, with the sum of the mass percentages of each component being 100%.

3. The method for preparing thick-film high-resistivity resistors based on Ts gradient and the three simultaneous principles as described in claim 1 achieves a sheet resistance range of 10Ω / square to 1MΩ / square.

4. The method for preparing a thick-film high-resistivity resistor based on the Ts gradient and the three-simultaneity principle according to claim 1, characterized in that, The glass phase softening point temperature range of the protective layer slurry is 350-500°C.

5. The method for preparing a thick-film high-resistivity resistor based on the Ts gradient and the three-simultaneity principle according to claim 1, characterized in that, The glass phase softening temperature range of the end slurry is 500-600°C.

6. The method for preparing a thick-film high-resistivity resistor based on the Ts gradient and the three-simultaneity principle according to claim 1, characterized in that, The glass phase softening temperature range of the resistance paste is 620-750°C.

7. The method for preparing a thick-film high-resistivity resistor based on the Ts gradient and the three-simultaneity principle according to claim 1, characterized in that, The composite powder contains at least two glass powders with different glass softening point temperatures, wherein the glass powder with the highest glass softening point temperature in the composite powder has a glass phase softening point temperature range of 700-800°C, and the glass powder with the lowest glass softening point temperature in the composite powder has a glass phase softening point temperature range of 450-550°C.

8. The method for preparing a thick-film high-resistivity resistor based on the Ts gradient and the three-simultaneity principle according to claim 1, characterized in that, The end-point slurry is prepared by mixing 9-13% of a special glass phase modified with RuO2, 61-67% of compound silver powder, and 22-28% of an organic carrier, with the sum of the mass percentages of each component being 100%.

9. A thick-film high-resistivity resistor prepared according to any one of claims 1 to 8 based on the Ts gradient and the three-simultaneity principle, characterized in that, The resistance ranges from 10Ω / square to 1MΩ / square.

Citation Information

Patent Citations

  • Thermistor element and manufacturing method thereof

    CN114121392A

  • Electrode composite and electronic component

    JP2004088019A